The evolution of selenium hyperaccumulation in Stanleya (Brassicaceae) - Cappa, Jennifer JoCarole, author; Simmons, Mark P., advisor; Pilon-Smits, Elizabeth A. H., advisor; Angert, Amy L., committee member; McKay, John, committee member (Colorado State University. Libraries, 2014)
Elemental hyperaccumulation is a fascinating trait found in at least 515 angiosperm species. Hyperaccumulation is the uptake of a metal/metalloid to concentrations 50-100x greater than surrounding vegetation. This equates to 0.01-1% dry weight (DW) depending on the element. Studies to date have identified 11 elements that are hyperaccumulated including arsenic, cadmium, cobalt, chromium, copper, lead, manganese, molybdenum, nickel, selenium (Se) and zinc. My research focuses on Se hyperaccumulation in the genus Stanleya (Brassicaceae). The threshold for Se hyperaccumulation is 1,000 mg Se kg-1 DW or 0.1% DW. Stanleya is a small genus comprised of seven species all endemic to the western United States. Stanleya pinnata is a Se hyperaccumulator and includes four varieties. I tested to what extent the species in Stanleya accumulate and tolerate Se both in the field and in a common-garden study. In the field collected samples only S. pinnata var. pinnata had Se levels >0.1% DW. Within S. pinnata var. pinnata, I found a geographic pattern related to Se hyperaccumulation where the highest accumulating populations are found on the eastern side of the Continental Divide. In the greenhouse S. pinnata var. pinnata accumulated the most Se within the genus, in both the young leaves and roots. I also discovered a polyploidy event within S. pinnata. All varieties of S. pinnata collected on the western slope of the Rocky Mountains were tetraploid and all but one population collected from the eastern slope of the Rocky Mountains were diploid. However, when tested, genome size did not correlate with Se hyperaccumulation capacity in S. pinnata. I isolated DNA from the field collected leaves and conducted a phylogenetic analysis using four nuclear gene regions and fifteen morphological characters. Using the phylogeny, I conducted an ancestral-reconstruction analysis to predict the ancestral states for Se related traits in a parsimony framework. I infer from the results that tolerance preceded hyperaccumulation in the evolution of Se hyperaccumulation in Stanleya and that hyperaccumulation evolved in an ancestor of the S. pinnata/bipinnata clade. Lastly, I conducted a comparative transcriptomic analysis between S. pinnata var. pinnata and S. elata, a non-hyperaccumulator. I found higher transcript levels for many of the enzymes involved in sulfur (S) transport and assimilation in S. pinnata relative to S. elata. Surprisingly, I found high constitutive expression for many of the S assimilation enzymes in the roots of S. pinnata, particularly an isoform of ATP sulfurylase. I also found high constitutive expression for sulfate transporter 1;2 in the roots of S. pinnata. Based on these data I infer that S. pinnata assimilates Se in the root and that sulfate transporter 1;2 and ATP sulfurylase 2 may be key enzymes in Se hyperaccumulation in S. pinnata. Taken together these data, in conjunction with previous work, help provide a better understanding of the evolution of Se hyperaccumulation in Stanleya at the physiological, phylogenetic and transcriptional levels.
Keywords: ancestral reconstruction; evolution; phylogenetics; selenium; Stanleya; transcriptome